Területi egyenlőtlenségek dimenziói. Adalékok egy „kvázi-elmélethez” - Nemes Nagy, József (Tér és Társadalom, 1990)
Spatial inequality is a central and at the same time, the most debated concept in spatial development. The present paper discusses theoretical and methodological issues related to this concept as well as problems related to spatial development policy in Hungary. As the concept of space is inseparable from the concept of inequality, all socio-spatial theories have their core or basis in some kind of inequality theory. The author identifies seven characteristic dimensions of spatial inequalities: inequalities in location, in quantities, in qualities, in hierarchical position, in structure, in connections, and in relationships. An important methodological problem of research into spatial inequalities is spatial aggregation, i.e. defming the spatial level or units of analyses. This question is studied by concrete examples in the paper. As for spatial development policy in Hungary, the author considers the „negation of space" (the power of „exterritorial" forces over the „territory") as a fundamental deforming feature of the previous socio-political mechanism. The predominance of ideology and politics in all spheres of society and the centralized system of control, which served it, represent the most important causes of this deformation. In order to counterbalance it the building up of a local self-governmental system is an outstanding task, which, presumably, can only become a well-operating basic institution of the new political system on the make, as a result of a long–several decades–learning process.